Analyzing and classifying risks: a case-study in the furniture industry - Leão, Celina Pinto (2019)
In this work we propose a methodology which permits the risk analysis and classification of occupational accidents in industrial settings. Data used in this study corresponds to accidents that occurred in the furniture industry in Portugal in 2010. A loss random variable is constructed in order to model the number of lost days implied by different contact modes of injuries in industry. The corresponding risk measures, such as Value-at-Risk, expected loss, loss variance and exceedance probabilities are determined in order to analyze and classify the contact modes according to their risk level, allowing the identification of the most problematic and the less problematic accident category in this industry. Contact with cutting, sharp, rough material was the most problematic whereas contact with electrical current, temperature, hazardous substance was the one with lower risk level.